Effects of the Doping of La and Ce in the Pt/B-TiO2 Catalyst in Selective Oxidation Reaction of Glycerol - Zhihui Wang; Xueqiong Zhang; Bo Hai; Hao Zhang; Lijun Ding (Crystals)
The increased production of biodiesel results in a corresponding rise in the production of glycerol (GLY) as a by-product. The selective oxidation of glycerol can yield relatively simple products under mild reaction conditions, offering high added value and positioning it as one of the most promising methods for industrialization. In this study, we employed black titanium dioxide (B-TiO2) as a support and deposited platinum (Pt) to create a noble metal-supported catalyst. Lanthanum (La) or cerium (Ce) was doped into B-TiO2 to enhance the concentration of oxygen vacancies in the support, thereby improving catalyst activity. Throughout the research process, we also investigated the impact of varying amounts of La or Ce doping on catalyst performance. Analysis of the catalytic experimental data revealed that Pt/30%Ce-B-TiO2 exhibited the highest catalytic performance. Structural analysis of the catalysts showed that the synergistic effect between Pt0 and oxygen vacancies contributed to enhancing catalyst activity.